MODEL KOMUNIKASI DIGITAL POLDA LAMPUNG DALAM MENGELOLA INFORMASI PUBLIK MELALUI WEBSITE POLDALAMPUNG.COM - Arioen, Refi; Suhaeri, Dade; Wijono, Allen Widyawati; Lutfi, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2025)
Public information disclosure requires the Lampung Regional Police to optimize its website as a digital communication channel; however, the communication pattern formed through poldalampung.com has not been clearly mapped. This study aims to describe Polda Lampung’s organizational communication model in managing public information via poldalampung.com. Using a qualitative case-study design, data were collected through in-depth interviews with officials and staff of the Public Relations Division, observation of the website’s interface and features, and content analysis of news, announcements, and service information. Data were analyzed through data reduction, data display, and conclusion drawing, with attention to the characteristics of linear, interactional, and transactional communication models. The findings indicate that website-based communication is still dominated by a one-way linear pattern, while interactional elements appear only to a limited extent through complaint and information-request channels that are asynchronous and largely administrative. Dialogic and simultaneous transactional communication is not yet evident. These results imply the need to strengthen the website’s function as a space for dialogue by adding interactive features and improving responsiveness, so that Polda Lampung’s public communication becomes more participatory and aligned with the principles of information openness in the digital era.